Bronchogenic cyst mimicking an adrenal mass in the retroperitoneal region: Report of a rare case - Gulay Bulut; Mehmet Deniz Bulut; Inci Bahadır; Çetin Kotan (Wolters Kluwer Medknow Publications, 2015)
We report the surgical excision of a retroperitoneal bronchogenic cyst that presented as a nonfunctioning left adrenal mass in a 25-year-old woman with continuous pain in the left flank. Preoperative biochemical testing confirmed that the mass was nonfunctional. Bronchogenic cysts are mostly benign congenital abnormalities that originate from the remnants of the primitive foregut and typically occur in the lung. Subdiaphragmatic and especially, retroperitoneal locations are rare. Despite the rarity of this pathologic entity, bronchogenic cysts should be considered in the differential diagnosis of retroperitoneal cystic lesions. Diagnosis must be definitively confirmed by histology.